Best management practices for a mangrove-friendly shrimp farming. - Baliao, Dan D.; Tookwinas, S. (Tigbauan, Iloilo SEAFDEC Aquaculture Department, 2002)
Aquaculture Extension Manual no. 35
Keywords: Philippines; Shrimp culture--Philippines.; Mangrove; Giant tiger shrimp culture